Evaluation of atmospheric boundary layer in open-loop boundary layer wind tunnel experiment - Vikneshvaran, .; Sheikh Ahmad Zaki, .; Nurizzatul Atikha, Rahmat; Mohamed Sukri, Mat Ali; Fitri, Yakub (Akademi Baru, 2020)
The present work discussed the development of the quasi-atmospheric boundary layer in an open-loop boundary layer wind tunnel over a smooth surface. The working section of the wind tunnel which is 1 m high and 9 m long is divided into three parts of 3 m long each. A constant temperature anemometer (CTA) hot wire was used to measure the flow velocity inside the test section. The wind speed of the wind tunnel was set at 10 m/s. The measurement was performed in three streamwise positions located in the three respective parts. The profiles of the streamwise velocity, standard deviation, and skewness that were obtained at the three streamwise positions revealed that the boundary layer height was developing from the upstream to the downstream positions in the wind tunnel. Additionally, flow uniformity and turbulence intensity of the inflow condition that was obtained in the first part of the test section were 7.1% and 6.4%, respectively.